A new high-altitude species of Penaincisalia Johnson, 1990 (Lepidoptera, Lycaenidae) from the Peruvian Andes - Bálint, Zsolt; Boyer, Pierre; Farfán, Jackie; Cerdeña, José; Pyrcz, Tomasz W. (Zootaxa, 2022)
A new Penelfin species, Penaincisalia jadwigae sp. nov. is described from very high elevations, 4510–4620 m, in the Department of Huancavelica, Peru. Superficially it is somewhat similar to P. perezi Bálint, 2001, but can easily be recognized by wing colour and pattern. A key for the identification of species in the Penaincisalia s. str. group with orange dorsal wing surface colouration is provided. A list of the local butterfly fauna is given, and spatial distribution, thermal regulation and discoloration are briefly discussed. The taxon Shapiroana matusikorum Johnson, 1992 is reinstated from synonymy with Penaincisalia aurulenta Johnson, 1990, as Rhamma matusikorum (Johnson, 1992), stat. rev., comb. n. 17 figures are provided.